Intercultural Education in School and Recognition of the Other A Educação Intercultural Na Escola e o Reconhecimento do Outro Diferente - Isabela Cabral Félix de Sousa (Arizona State University, 2004)
This article describes a potential project of intercultural education for schools. It begins by emphasizing the growing importance of this kind of project in an era of globalization. Then, I describe some educational proposals toward the construction of a new way to look to oneself and "the other." Third, I discuss the possibility that a project of this nature may be resisted since it challenges the status quo. Finally, the article stresses that the implementation of this project depends on educational policies and the efforts of the total society. Este artigo delinea o que pode ser o projeto da educação intercultural na escola. Começa enfatizando a crescente importância deste tipo de projeto na era da globalização. Depois, descreve algumas propostas educacionais na construção de um novo olhar para si e para o outro. Em terceiro lugar, discute a possiblidade que um projeto desta natureza tem de provocar resistências porque desafia o status quo. Finalmente, o artigo ressalta que a implementação deste projeto depende de políticas educacionais e do empenho de toda a sociedade.